ChemInform Abstract: Multichromophoric Electrochromic Polymers: Color Tuning of Conjugated Polymers Through the Side Chain Functionalization Approach. Issue 27 (8th July 2014) - Beverina, L.; Pagani, G. A.; Sassi, M.
Abstract Review: 164 refs.